An improved micro-thermo-mechanics model for shape memory alloys: analysis and applications. (11th May 2020) - Manzoor, Tareq; Zafar, Muhammad; Manzoor, Sanaullah; Manzoor, Habib Ullah; Ali, Muddassir; Kim, Woo Young
Abstract: In this paper, micro-mechanics of shape memory alloys (SMA) is investigated for design of smart structure and devices, based upon three dimensional constitutive model. In this work, a micro-mechanics based approach is presented. A modification in temperature field of the above model is proposed, where temperature is taken as function of time. Thermal parameters corresponding to transformation temperatures are introduced here. The model solution is presented for the of a set of initial and boundary conditions based upon any type of thermal parameters. Three particular cases for different thermal and structural loading-stresses are presented here. The solution given here expresses the response of smart dampers for various thermal and structural loading conditions. Moreover, the applications of this system were also investigated.